AL-QUR’AN ITU MENJAGA DIRI: PERANAN REGULASI DIRI PENGHAFAL AL-QUR’AN - Lukmawati Lukmawati; Faisal Tanjung; Jhon Supriyanto (Psikis : Jurnal Psikologi Islami, 2017)
This research discussed about self regulation of Al-Qur'an reminder students at Rumah Qur'an Daarut Tarbiyah Palembang. This research used qualitative research with fenomenology design. The research result showed that after passing all the steps in self regulation to finish 30 chapters of Al-Qur'an so the eight research subjects got one same meaning of Al-Qur’an, that is Al-Qur'an is a way to protect their selves for instance: to protect their image/honor, to protect their purity by doing wudhu,to protect their eyes to see only  a good thing, to protect their behaviour, to protect their selves in order to not includedin a group of unreliable people who did not do what they said,to protect their akhlak and attitude, to protect their way to wear an appropriate clothes based on syar’i, and the last isto protect their behaviour in communicating with other people especially to the older people.